Synthesis and characterization of Al–Mg–Zn thin film alloys co‐deposited from vapour phase. Issue 5 (4th March 2013) - Voith, Michael; Mardare, Andrei I.; Hassel, Achim Walter
Abstract Mg–Zn thin film alloys were produced by thermal co‐evaporation using single source and dual source geometries. The films containing high amount of Zn (66 at.%) were prone to formation of metallic micro spheres on the surface when high evaporation rates (10 nm s−1) were used. The Mg–27.1 at.% Zn bulk alloy was found to be suitable for co‐deposition with Al for producing Al–Mg–Zn thin film alloys. A low Al concentration gradient (5 at.%) could be obtained along the sample due to the high deposition rates of Mg–Zn (7.5 nm s−1) combined with low Al deposition rates (0.2 nm s−1). The Al–Mg–Zn thin films showed an improved resistance against chemical attack when higher amounts of Al are used, as shown by downstream analytics investigations using a flat flow electrochemical cell coupled to an AAS system. <inline-graphic xlink:href="ark:/27927/pgg20q11xcb" content-type="pssa201200742-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />